Sensitivity and phase response of FBG based acousto-optic sensors for real-time MRI applications - Yaras, Yusuf Samet (OSA Contin, 2020)
Fiber Bragg grating (FBG) based sensors have recently been introduced to the field of magnetic resonance imaging (MRI). Real-time MRI applications demand highly amplitude and phase sensitive MRI compatible sensors. Thus, a model and detailed analysis of FBG based ultrasound detection are required for designing better performing sensors. A hybrid FBG model incorporating numerical and FEA methods was developed and used for sensitivity and linearity analysis. The transfer matrix method was used for the modeling of optical modulation whereas FEA was used for pressure field calculations within the grating. The model was verified through reflection spectrum and acoustic pressure sensitivity testing of two π-phase shifted FBGs in a side slope read-out configuration. The sensitivity curves with respect to the operation point on the side slope was characterized in terms of amplitude and phase, and nonlinearity of the phase response has been quantified. Lastly, the impact of phase linearity of the FBG based acousto-optic sensor was tested under MRI when the sensor was used as a position marker and an analog phase shifter based solution was demonstrated.